Net clinical benefit of oral anticoagulants in Korean atrial fibrillation patients with low to intermediate stroke risk: A report from the Clinical Survey on Stroke Prevention in patients with Atrial Fibrillation (CS‐SPAF) - Jung, Moonki; Byeon, Kyeongmin; Kang, Ki‐Woon; Lee, Wang‐Soo; Kim, Sang Wook; Park, Yae Min; Hwang, You Mi; Lee, Sung Ho; Jin, Eun‐Sun; Roh, Seung‐Young; Kim, Jin Seok; Ahn, Jinhee; et al. (Journal of arrhythmia, 2023)
Background The balance of stroke risk reduction and potential bleeding risk associated with antithrombotic treatment (ATT) remains unclear in atrial fibrillation (AF) at non‐gender CHA2DS2‐VASc scores 0–1. A net clinical benefit (NCB) analysis of ATT may guide stroke prevention strategies in AF with non‐gender CHA2DS2‐VASc scores 0–1. Methods This multi‐center cohort study evaluated the clinical outcomes of treatment with a single antiplatelet (SAPT), vitamin K antagonist (VKA), and non‐VKA oral anticoagulant (NOAC) in non‐gender CHA2DS2‐VASc score 0–1 and further stratified by biomarker‐based ABCD score (Age [≥60 years], B‐type natriuretic peptide [BNP] or N‐terminal pro‐BNP [≥300 pg/mL], creatinine clearance [<50 mL/min], and dimension of the left atrium [≥45 mm]). The primary outcome was the NCB of ATT, including composite thrombotic events (ischemic stroke, systemic embolism, and myocardial infarction) and major bleeding events. Results We included 2465 patients (age 56.2 ± 9.5 years; female 27.0%) followed‐up for 4.0 ± 2.8 years, of whom 661 (26.8%) were treated with SAPT; 423 (17.2%) with VKA; and 1040 (42.2%) with NOAC. With detailed risk stratification using the ABCD score, NOAC showed a significant positive NCB compared with the other ATTs (SAPT vs. NOAC, NCB 2.01, 95% confidence interval [CI] 0.37–4.66; VKA vs. NOAC, NCB 2.38, 95% CI 0.56–5.40) in ABCD score ≥1. ATT failed to show a positive NCB in patients with truly low stroke risk (ABCD score = 0). Conclusions In the Korean AF cohort at non‐gender CHA2DS2‐VASc scores 0–1, NOAC showed significant NCB advantages over VKA or SAPT with ABCD score ≥1. Non‐vitamin K antagonist oral anticoagulants (NOACs) showed a statistically significant net clinical benefit (NCB) in comparison with single antiplatelet therapy (SAPT) and vitamin K antagonist therpay (VKA) in patients with non‐gender CHA2DS2‐VASc score = 1 & ABCD score = 1.